PREVALENCE OF FASCIOLIASIS AND PARAMPHISTOMIASIS IN DAIRY CATTLE IN OXAPAMPA, PASCO - Chávez V., Amanda (2010)
The aim of the present study was to estimate the prevalence of Fasciola hepatica and a Paramphistomide in dairy cattle from the districts of Huancabamba, Chontabamba and Oxapampa, province of Oxapampa, Pasco. A total of 408 fecal samples cattle were collected during May and November 2006 and processed by the Rapid Sedimentation test. Eggs were differentiated by the morphologic characteristics of each species. The district and age group (2-4, 5-6 y >6 years) were considered in the statistical analysis. The results showed prevalences of 10.0 ± 2.9% for F. hepatica and 28.4 ± 4.4% for a fluke of the Paramphistomidae family, without statistical difference due to district and age group, with the exception of Paramphistomide where animals older than 6 years of age had more possibilities of getting infected than younger animals (p<0.025).